Russian young scientists in the context of the transition to the knowledge economy - Mishchenko, V. V.; Mishchenko, I. V. (Journal of Economic Research & Business Administration, 2022)
Science is the central link of a new type of economy – the economics of knowledge and high technologies. However, modern Russian science today faces a number of pressing problems, among which the personnel issue is central. The article is about young scientists. It is through them that the continuity of generations is ensured, traditions are preserved and new things are introduced into modern science. The purpose of the scientific research is to analyze the dynamics of young scientists in Russia, identify the problems they face today, as well as develop a number of recommendations to increase the attractiveness of scientific activities among young people. The article analyzes the dynamics and structure of scientific personnel of higher education in the period from 2010 to 2019. It was revealed, that the structure is changing in favor of the younger generation, but the number of researchers, including young ones, is steadily decreasing, jeopardizing Russia’s transition to the knowledge economy. The article reveals the factors that influence this process. Among them, one can single out both the internal – demographic decline, low wages of young scientists, the reform of higher education, and the external factor – the globalization of the economy. Significant measures are being taken to eliminate these factors both at the level of the Russian Federation Government and at the level of individual scientific and educational organizations. However, the analysis showed that these measures have a limited range of actions and do not completely solve the problem of young scientific personnel. In this regard, the authors developed a number of recommendations that will increase the attractiveness of science among young people, reduce the outflow of promising personnel from the country, and attract foreigners to Russian science. Key words: science, young people, factors, support tools, financing.